الحساسية الانفعالية وعلاقتها بالمهارات الاجتماعية لدى الأطفال المتأخرين لغويا - الفقي، مريم محمد أحمد Alfeqi, Mariam Mohammed Ahmed (جامعة الزقازيق - كلية التربية, 2022)
هدف البحث الحالي إلى التعرف على العلاقة بين الحساسية الانفعالية والمهارات الاجتماعية لدى الأطفال المتأخرين لغوياً، وتكونت عينة البحث من (٦٥) طفلاً وطفلة من المتأخرين لغوياً (33) ذكور و(32) إناث بعمر زمني من (٦-8) سنوات، واستخدمت الباحثة مقياس الحساسية الانفعالية للأطفال المتأخرين لغوياً إعداد الباحثة، ومقياس المهارات الاجتماعية للأطفال المتأخرين لغوياً إعداد الباحثة. وتوصلت نتائج البحث إلى وجود علاقة ارتباطية سالبة بين الدرجات الكلية للحساسية الانفعالية والدرجات الكلية للمهارات الاجتماعية، كما توصلت النتائج إلى أن مستوي درجات العينة (من الأطفال المتأخرين لغوياً) على مقياس الحساسية الانفعالية ( كل بعد من الأبعاد، والدرجة الكلية للمقياس) مستوي متوسط، بينما أظهرت النتائج أن مستوي درجات العينة (من الأطفال المتأخرين لغوياً) كل من البعد الأول (التواصل مع الأخرين)، والبعد الثاني (التعاطف)، والبعد الثالث (التعاون)، والمهارات الاجتماعية ككل (الدرجات الكلية) مستوي متوسط، بينما كان مستوي درجات العينة (من الأطفال المتأخرين لغوياً) في كل من: البعد الرابع (الضبط الانفعالي)، والبعد الخامس (الضبط الاجتماعي) مستوي منخفض. وكذلك جاءت نتائج البحث تؤكد عدم وجود فروق بين الذكور والإناث في الأبعاد الثلاثة الأولي (الفسيولوجي –النفسي-ضعف الثقة بالنفس) من أبعاد الحساسية الانفعالية، بينما أظهر الذكور مستوي أعلى من الإناث في مهارات الضبط والمرونة وفي الحساسية الانفعالية ككل. كما أكدت النتائج عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات الذكور والإناث في الأبعاد والدرجات الكلية لمقياس المهارات الاجتماعية.
The research aimed to identify the relationship between emotional sensitivity and social skills among the children with language delay, the research sample consisted of (65) children with language delay, divided to (33) males and (32) females aged from (6-8) years, the researcher used the emotional sensitivity scale for children with language delay (prepared by the researcher), and a scale of social skills for children with language delay (prepared by the researcher); The results of the research showed that there is a negative correlation between the total degrees of emotional sensitivity and the total degrees of social skills. the results also found that the level of the sample scores (of the children with language delay) on the emotional sensitivity scale (in each of the dimensions and the total degree of the scale), is an intermediate level. The results also showed that the level of the sample scores (of children with language delay) in each of the first dimension (communication with others), the second dimension (sympathy), the third dimension (cooperation), and social skills as a whole (total scores), is an intermediate level, While the level of the sample scores (of children with language delay) in the fourth dimension (emotional control) and the fifth dimension (social control), was a low level. The results of the research also confirmed the absence of differences between males and females in the three dimensions (physiological - psychological - the weakness of self-confidence) of the dimensions of emotional sensitivity, while males showed a higher level than females in the adjustment and flexibility skills, and in emotional sensitivity as a whole. The results also showed that there were no statistically significant differences between the average scores of males and females in all dimensions and total scores of the social skills scale.
Keywords: التربية الخاصة -- الأطفال المعوقون -- الاضطرابات اللغوية -- التواصل الاجتماعي -- المهارات الحياتية